Hubungan Faktor Sanitasi Total Berbasis Masyarakat dengan kejadian stunting pada Balita di Wilayah Kerja Puskesmas Talagamori - Cindy Casilia Marfati; Osnawati H. Marsaoly; Arif Mustofa (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Stunting is a chronic nutritional problem in toddlers characterized by shorter body height that is not appropriate for their age. Stunting can be caused by many factors such as socio- economic conditions, maternal nutrition during pregnancy, the health of the baby, and lack of nutritional intake for the baby. Toddlers who experience stunting in the future will experience difficulties in achieving optimal physical and cognitive development. This research aims to determine the relationship between several variables on the incidence of stunting among toddlers in the Talagamori Community Health Center working area. This type of research is descriptive analytics using a case control approach. The number of samples used in this research was 150 people and total sampling was carried out using inclusion and exclusion criteria. The independent variables in this study are open defecation behavior, washing hands with soap, managing household drinking water and food, managing household waste and managing household liquid waste. Meanwhile, the dependent variable is the incidence of stunting. The results of the study showed that there was a relationship between open defecation behavior and the incidence of stunting (p=0.002). There is no relationship between washing hands with soap and the incidence of stunting (p=0.130). There is no relationship between household drinking water and food management and the incidence of stunting (p=0.336). There is a relationship between household waste management and the incidence of stunting (p=0.020). There is a relationship between household liquid waste management and the incidence of stunting (p=0.017). Community-Based Total Sanitation (STBM) is the first step in ensuring family hygiene and health. Good sanitation can prevent families, especially children under five, from malnutrition and infectious disease infections.